Multiple Lenses of N-Isotopes Reveal Active Dissolved Organic Nitrogen Cycling in a Subtropical Estuary and Marginal Sea - Xiaosong Zhong; Maojun Yan; Wenqi Xu; Zhenwei Yan; Feng Xu; Shuhang Dong; Yu Xin; Xiaoyong Shi (Frontiers in Marine Science, 2022)
Dissolved organic nitrogen (DON) is an important component of the marine nitrogen (N) inventory and plays an essential role in N cycling in global estuaries and marginal seas. Understanding DON cycling is important but challenging. Global estuaries and marginal seas are experiencing significant anthropogenic impacts and have intensive physical/biochemical gradients. Therefore, high-quality DON concentration and N-isotope (δ 15 N–DON) data are very difficult to obtain. To enrich this knowledge, we take the Changjiang Estuary and the adjacent East China Sea shelf seas as a representative example and analyzed multiple isotopes and the concentrations of nitrate ( N O 3 − ), particulate nitrogen (PN), and DON. N isotopes combined with optimum multiparameter analysis proved to be very informative. This integrated analysis discriminates active DON production and consumption from a seemingly conservative distribution pattern of DON. The study area was divided into DON production zones 1 and 2 (P-zone 1 and 2) and DON consumption zones 1 and 2 (C-zone 1 and 2). For P-zone 1, the PN-originated DON elevated the δ 15 N–DON, while in P-zone 2, the DON excreted by phytoplankton was characterized by low δ 15 N and lowered δ 15 N–DON. DON consumption occurred in the N O 3 − depleted surface waters (C-zone 1) as well as the shelf middle and bottom waters (C-zone 2). This study discovers and consolidates the active and dynamical zoning of DON cycling from the estuary to the offshore marginal sea and establishes a useful means that is of valuable reference to DON cycling studies in global estuaries and marginal seas.